“Dear Neighbours ...” a comparative exploration of approaches to managing risks related to hazardous incidents and critical infrastructure outages - Krings, Susanne (ERDKUNDE, 2018)
This paper explores the management of two types of risks which derive from the disruption of normal operations in technical installations: one is related to hazardous incidents, i.e. failures during the course of which substances rated as hazardous are emitted into the environment; the other is related to outages of critical infrastructures, which involve the unavailability of goods and services taken to be essential. Both risks are objects of political debate and administrative action in Germany. The practice of distributing informative brochures in the neighbourhood of a power plant serves as a starting point for a comparative exploration of approaches to handling risks associated with sites prone to hazardous incidents and with critical infrastructures. Starting from here, the paper addresses characteristic features of the practices applied in accordance with the two risk management approaches. The empirical basis comprises a variety of instruments, some more and some less binding, which seek to shape risk management practices, such as laws, recommendations or political strategies. The paper first addresses the federal level (and the influence of the European Union) before the scope is widened to include the other administrative levels, i.e. states and municipalities. The exploration first considers the ways used to designate the relevant facilities. While hazardous sites are bindingly identified at all levels on the basis of a common legal framework, determination of critical infrastructures is considered a context-dependent undertaking and is only partially regulated. Further, it is ascertained that the approaches divergently conceptualize the relations between the ‘source of risk’ and who or what is ‘at risk’. Physical distance (or proximity) is treated as paramount with regard to risks related hazardous incidents, whereas a functional relationship, i.e. a degree of dependency, is taken to be decisive in the context of critical infrastructures. Finally, the two approaches are shown to exhibit diverging attitudes to providing site-specific information to the public. The hazardousness of a site is designated to be public information but its criticality, on the contrary, is to remain classified. As expounded in the last section, these conceptional differences may lead to practical difficulties in civil protection operations.